Interactions between the 5′ UTR mRNA of the spe2 gene and spermidine regulate translation in S. pombe - Sun, Wenxia (RNA, 2020)
The 5′ untranslated regions (5′ UTR) of mRNAs play an important role in the eukaryotic translation initiation process. Additional levels of translational regulation may be mediated through interactions between structured mRNAs that can adopt interchangeable secondary or tertiary structures and the regulatory protein/RNA factors or components of the translational apparatus. Here we report a regulatory function of the 5′ UTR mRNA of the spe2 gene (SAM decarboxylase) in polyamine metabolism of the fission yeast Schizosaccharomyces pombe. Reporter assays, biochemical experiments, and mutational analysis demonstrate that this 5′ UTR mRNA of spe2 can bind to spermidine to regulate translation. A tertiary structure transition in the 5′ UTR RNA upon spermidine binding is essential for translation regulation. This study provides biochemical evidence for spermidine binding to regulate translation of the spe2 gene through interactions with the 5′ UTR mRNA. The identification of such a regulatory RNA that is directly associated with an essential eukaryotic metabolic process suggests that other ligand-binding RNAs may also contribute to eukaryotic gene regulation.